Stanley Hauerwas and the Liberal Protestant Project - Reno, Russell R. (Modern theology, 2012)
Stanley Hauerwas has been seen as a staunch opponent of liberal Protestantism. However his upbringing, education, and theological points of emphasis suggest that his work is best understood as in internal critique of liberal Protestantism, one that follows in a tradition of twentieth-century theological renewals.